Effects of Homogenization Scheme of TiO2 Screen-Printing Paste for Dye-Sensitized Solar Cells - Seigo Ito; Kaoru Takahashi; Shin-ich Yusa; Takahiro Imamura; Kenji Tanimoto (International Journal of Photoenergy)
TiO2 porous electrodes have been fabricated for photoelectrodes in dye-sensitized solar cells (DSCs) using TiO2 screen-printing paste from nanocrystalline TiO2 powder dried from the synthesized sol. We prepared the TiO2 screen-printing paste by two different methods to disperse the nanocrystalline TiO2 powder: a “ball-milling route” and a “mortal-grinding route.” The TiO2 ball-milling (TiO2-BM) route gave monodisperse TiO2 nanoparticles, resulting in high photocurrent density (14.2 mA cm−2) and high photoconversion efficiency (8.27%). On the other hand, the TiO2 mortal-grinding (TiO2-MG) route gave large aggregate of TiO2 nanoparticles, resulting in low photocurrent density (11.5 mA cm−2) and low photoconversion efficiency (6.43%). To analyze the photovoltaic characteristics, we measured the incident photon-to-current efficiency, light absorption spectroscopy, and electrical impedance spectroscopy of DSCs.